Unveiling the Cultural Tapestry: Javanese Women's Roles in the 1960s as Portrayed in the Series Gadis Kretek - Taufiqurrahma, Chullatussundusia; Reswara, Gandhik Yanuar; M, Muhammad Galih; Maharani, Jingga Kirana Diah (Jurnal Ilmiah Wahana Pendidikan, 2024)
Indonesia is a country with an extraordinary cultural diversity. One of the dominant cultures is the Java culture, where the Java community has standards and special values that apply in everyday life, including the role and position of Java women. One representation of the social and cultural changes of Java is the series 'Gadis Kretek', which tells the life of Java girls in the 1960s. One of the characters from the series 'Gadis Kretek' depicts Java women in this transitional period. In the context of Java culture, women have a rather dominant role in everyday life, despite the old view that women in Java culture tend to be behind the screens. The existence of such a mindset then becomes a special challenge for Java women to be able to show themselves and make more contributions in various aspects of life. This study focuses on "Gadis Kretek" as a work that describes the roles and experiences of Java women in the 1960s. It helps us gain a deeper understanding of the gender role, challenges, and struggles faced by women at this critical period in Indonesian history. Besides, it also provides insight into how these roles and experiences have shaped the Java and Indonesian societies in general as we know them today. By understanding the 'Gadis Kretek', we can bridge the gaps in knowledge about the role of Java women in history and unleash harmful prejudices and stereotypes in Indonesian culture.